Establishment health post and training cadre Santri Husada Al ‘atsar Quranic boarding school Caturharjo, Pandak, Bantul - Yuniasih, Dewi; Agustin, Helfi; Rahma, Shafa Sabilla; Fatimah, Siti; Awisarita , Wiwara; Widiana, Herlina Siwi (Universitas Ahmad Dahlan, 2024)
The establishment of a boarding school health post aims to create a healthy behavior of residents and a healthy environment through increasing the knowledge and skills of students so that they are able to help themselves and others. Activities consist of preventing communicable or non-communicable diseases, improving health through habituation of physical activity, stress management, eating nutritious and balanced food, preventing and controlling health risks in the Islamic boarding school environment such as monitoring mosquito larvae, managing waste and waste properly, maintaining cleanliness of body, food and environment, etc.The implementation of community service was July 17th until Spetember 1st , 2022. Located in the Al a’tsar Islamic boarding school at Banyu Urip- Caturharjo, Pandak Bantul, This community service activity was assisted by 10 students, consisting of 2 students from undergraduate of the public health, 4 students from the psychology, 4 students from medical faculty. Exit strategy by collaboration with the Pandak 2 health center. The existence of the boarding school helath post is expected to motivate students and techers to be more independent in terms of disease prevention, helath improvement, simple treatment and post-treatment health recovery in health care facilities